The effects of mandatory IFRS adoption on financial analysts' forecast: Evidence from Jordan - Najeb Masoud (Cogent Business & Management, 2017)
This paper examines the effect of the mandatory adoption of International Financial Reporting Standards (IFRS) on the ability of financial analysts to forecast earnings accurately in Jordan during the period 2002–2013. The methodology involved the use of a panel data model and the regression with temporal “dummy” variables in order to test the hypotheses formulated for the study. The research findings show after mandatory IFRS adoption has improvements in the ability of analysts to forecast earnings (decrease in error and dispersion). These findings are evidence of an improvement in earnings quality of Jordan listed firms after the collective requirement to adopt IFRS. The evidence from the study also shows the debate on the desirability of the current move towards one global set of accounting standards as results are robust to several changes in model specifications. The study contributes to the previous finding dealing with the additional quality informational content stemming and, more specifically the quality of earnings from mandatory of IFRS adoption. The originality of this study consists primarily in the use of a long analysis period following the implementation of IFRS that should reduce divergences between analysts, causing a decrease in earnings forecast error and dispersion. Therefore, this study examines only the Jordan context; it's interesting for future research to study the effect of IFRS mandatory adoption for several countries, especially in emerging market.
Keywords: 650